TENSILE PROPERTIES OF LIGNOCELLULOSIC COMPOSITES: A COMPARISON ANALYSIS BETWEEN NATURAL FIBER COMPOSITES (NFCs) AND MEDIUM DENSITY FIBER (MDF) - Fajrin, Jauhar; Herlina Sari, Nasmi (JURNAL SPEKTRAN, 2018)
This paper presents an experimental investigation on the tensile properties of lignocellulosic composites; which is specifically compare the tensile properties of composites derived from natural fibers (jute, sisal and hemp) to a medium density fiber (MDF). The study was conducted experimentally by performing tensile tests according to BS EN ISO 527-2 using a MTS machine. Five specimens were prepared for each composite laminate. The results show that the tensile properties of lignocellulosic composites derived from natural fibers are superior to medium density fiber. The tensile strength of medium density fiber is 17.1 MPa; while sisal, jute and hemp fiber composite has the value of 40.25 MPa, 37.25 MPa and 31.37 MPa, respectively. Further, medium density fiber has the elastic modulus of 2603 MPa; while jute, sisal and hemp fiber composite has the values of 4592 MPa, 3643 MPa and 3048 MPa, respectively. Natural fiber composites also possess higher Poisson’s ratio which is greater than 0.36, while medium density fiber has the value of 0.25. Keywords : Lignocellulosic composite, tensile properties, Poisson ratio, elastic modulus